Model Predictive Control for Omnidirectional Small Size Robot with Motor and Non-Slipping Constraints - Pinheiro, Felipe; Máximo, Marcos; Yoneyama, Takashi (Anais do Simpósio Brasileiro de Robótica e Simpósio Latino Americano de Robótica (SBR/LARS); 2019: Anais do VII Simpósio Brasileiro de Robótica e XVI Simpósio Latino Americano de Robótica, 2019)
Model Predictive Control for Omnidirectional Small Size Robot with Motor and Non-Slipping Constraints